Early oral cavity cancer: The prognostic factors and impact of adjuvant radiation on survival. Issue 10 (24th July 2019) - Rajappa, Suhas K.; Maheshwari, Udip; Ram, Dharma; Koyyala, Venkata P. B.; Mandal, Ghanashyam; Goyal, Sumit; Kumar, Rajeev; Dewan, Ajay K.
Abstract: Background: Early oral cavity cancer has good prognosis but recurrence in them is still not uncommon. There is no general consensus on the prognostic factors and adjuvant therapy that would have a significant impact on survival. Methods: A retrospective analysis of early oral cavity cancer patients during the time period 2009‐2017. The data regarding demographics, histopathological features, and recurrence patterns were collected and analyzed. Results: Depth of invasion (DOI) was the most important prognostic factor among all the factors analyzed. Further analysis showed that addition of adjuvant radiotherapy for patients with DOI >5 mm did not show survival benefits ( P = .73). Another subset analysis of patients with DOI >10 mm also did not show any survival advantage with adjuvant therapy P = .24. Conclusion: There is no benefit of adding adjuvant RT in patients with DOI > 5 mm or in patients who were upstaged to T3 based only on DOI.